Preemption, start-up decisions and the firms' capital structure - Michele Moretto; Paolo M. Panteghini (Center for Economic Studies and ifo Institute (CESifo), 2007)
In this article, we analyse the interactions between financial and start-up decisions in an oligopolistic framework, where firms compete to enter a new market. We show that preemption can substantially reduce the negative effects of credit rationing on start-up investment decisions.
Keywords: D92; G33; 330; Oligopol; Unternehmensgründung; Sunk Costs; Potenzieller Wettbewerb; Kapitalstruktur; Realoption; Theorie